1998
DOI: 10.1016/s1074-5521(98)90005-9
|View full text |Cite
|
Sign up to set email alerts
|

Homologs of the vancomycin resistance d-Ala-d-Ala dipeptidase VanX in Streptomyces toyocaensis, Escherichia coli and Synechocystis: attributes of catalytic efficiency, stereoselectivity and regulation with implications for function

Abstract: The key residues of the EntVanX active site are strongly conserved in the VanX homologs, suggesting their active-site topologies are similar. StoVanX is a highly efficient D-Ala-D-Ala dipeptidase; its gene is located in a vanHAX operon, consistent with a vancomycin-immunity function. StoVanX is a potential source for the VanX found in gram-positive enterococci. The catalytic efficiencies of D-Ala-D-Ala hydrolysis for EcoVanX and SynVanX are 25-fold lower than for EntVanX, suggesting they have a role in cell-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 53 publications
3
95
0
1
Order By: Relevance
“…The latter include D-alanine (D-ala) and the D-alanine-D-alanine dipeptide (D-ala-D-ala) released during murein synthesis. The cycA gene (b4208), which encodes a transporter for D-ala, is under Nac control and the ddp operon (b1483-88), which encodes a transporter and a specific dipeptidase for D-ala-D-ala (10), is under NtrC control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter include D-alanine (D-ala) and the D-alanine-D-alanine dipeptide (D-ala-D-ala) released during murein synthesis. The cycA gene (b4208), which encodes a transporter for D-ala, is under Nac control and the ddp operon (b1483-88), which encodes a transporter and a specific dipeptidase for D-ala-D-ala (10), is under NtrC control.…”
Section: Discussionmentioning
confidence: 99%
“…The nac-28 disruption (2), which also deletes the nac promoter, was introduced directly into NCM3292 to yield the kanamycin-resistant strain NCM3596. The glnL(Up) and glnG alleles also were introduced into strain IADL310 (10) to yield strains NCM3700 and NCM3701, respectively. IADL310 carries at the attachment site a fusion of the ddp promoterregulatory region (12-287 bp upstream of the translational start for ddpX) to lacZ.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that PBP3, which is involved in septum formation, is down-regulated by RpoS upon entry into stationary phase. RpoS is also implicated in remodeling of crosslinks in the cell wall of stationary phase E. coli cells (38). The frequency of direct crosslinks between two diaminopimelate residues on adjacent peptidoglycan strands increases 6-fold in stationary phase, a change paralleled by a decrease in D-Ala-D-Ala crosslinks (39).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated the presence of the vanH, vanA, and vanX resis- tance genes in S. toyocaensis and other glycopeptide producing bacteria, precisely in the same orientation and with the same enzymatic activities as the orthologous genes that confer highlevel glycopeptide resistance in Enterococci (VRE) (35). The genes for vanHst, an ␣-ketoacid reductase required for D-lactate biosynthesis (36), vanAst, a D-Ala-D-lactate ligase (13,37) and vanXst, a D-Ala-D-Ala-specific dipeptidase (38), located at the 5Ј-end of the A47934 biosynthetic cluster, represent the first time antibiotic resistance genes have been unambiguously coupled to the biosynthesis genes in a glycopeptide-producing organism. These genes are both necessary and sufficient for host resistance to A47934 by predicted conversion D-Ala-D-Ala in the peptidoglycan layer to D-Ala-D-lactate.…”
Section: The Organization Of the E Domains Predicts A Stereochemistrymentioning
confidence: 99%